Representasi Perempuan Lajang melalui Karakter Lainy pada Film Kinda Pregnant - Husna Azzahra Zulfa; Elpa Hermawan; Ondy Ondy (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Women are an interesting subject of analysis in the media, especially in films. The status of single women, meaning those without a partner, is often accompanied by negative stigma and social pressure to meet societal expectations. This phenomenon is often perceived as a failure to fulfill one's expected role, thereby creating various challenges for single women. This study aims to examine the representation of singlewomen through the character Lainy in the film Kinda Pregnant, exploring how Lainydeals with social stigma and pressure related to her status. Using Stuart Hall's theory of representation, this study applies a descriptive qualitative method and a semiotic approach developed by Roland Barthes. This study analyzes 12 selected scenes to identify relevant themes, such as expectations, reproductive myths, social pressure, and negative stereotypes faced by single women. The analysis reveals that single women are often labeled as “old maids” and compared to the ideal married woman. In this context, Lainy is depicted as struggling against societal expectations regarding marriage and motherhood, while striving to find self-acceptance amid the stigma attached to her status. This study aims to provide insights into the challenges faced by single women in social and cultural contexts, emphasizing the importance of solidarity among women.